Low cost alternatives in commercial micropropagation of banana(musa spp.) - Faiza Mohamed (Centre for Plant Biotechnology and Molecular Biology,College of Horticulture, 2018)
Tissue culture banana plants have become an integral part of commercial banana production. Banana micropropagation is hampered by high unit cost of production, poor multiplication and low survival rates during acclimatization. To make a commercial micropropagation unit viable, cost of production of plantlets should be brought to minimum. The investigations on ‘Low cost alternatives in commercial micropropagation of banana’ was hence taken up at Centre for Plant Biotechnology and Molecular Biology, College of Horticulture from 2016-2018. The aim of the investigations was to reduce the cost of production in commercial micropropagation of banana. Studies were conducted in different cultivars like Attunendran (AAB), Nedunendran (AAB), Chengalikodan (AAB), Poovan (AAB), Njalipoovan (AB) and Grand Naine (AAA) which were commercially produced at CPBMB in the micropropagation unit. Established cultures of six cultivars in the 5th subculture cycle received from the commercial micropropagation of unit CPBMB were utilized for the study. The micropropagation protocols optimized for the six different cultivars at CPBMB were followed for production of plantlets. The clonal fidelity analysis standardized using specific ISSR marker at CPBMB was used to analyse the clonal fidelity of regenerants from S7 to S11 stage. Sucrose was substituted with common sugar @ 30gL-1 in MS multiplication and rooting media and shoot proliferation, rooting and root characters in different cultivars were studied. Common sugar was found equally good to sucrose and it did not influence shoot proliferation in different banana cultivars. Common sugar was also found equally good to sucrose in the rooting media recording 100 per cent rooting in all the six cultivars studied. Substitution of sucrose with common sugar had no significant influence in the days taken for root initials to appear. For number of primary roots produced, there was no significant difference in all the cultivars in the two media except Attunendran in which medium with common sugar produced more number of primary roots (8.41) than sucrose (6.75). Root length was higher in MS rooting medium with common sugar in cultivars like Chengalikodan, Njalipoovan and Grand Naine. Medium with common sugar produced more number of secondary roots in cultivar Chengalikodan while medium with sucrose produced more number of secondary roots in cultivars like Attunendran and Njalipoovan. When fifty per cent of agar was substituted with other solidifying agents like sago or isabgol, there was good solidification of MS medium. There was no significant variation in shoot proliferation in different cultivars when half of agar was substituted with isabgol or sago in the MS multiplication medium. Fifty per cent substitution of agar with isabgol or sago was found equally good to agar (100%) in rooting medium. Hundred per cent rooting was observed in the three different media combinations in all the cultivars. Substitution of 50 per cent agar with isabgol or sago showed no significant difference in days taken for root initials to appear, number of primary roots, number of secondary roots and root length in cultivars like Attunendran, Njalipoovan and Grand Naine. There was no difference in survival of plantlets in treatments with different low cost additives. When low cost carbon source and gelling materials were used instead of standard additives, there was 87 per cent reduction in media cost. Clonal fidelity was analysed using specific ISSR marker optimized at CPBMB as reported by Rajitha et al. (2015). Polymorphic amplicons were observed as subculture progressed from S9 – S11 in cultivars like Nedunendran, Attunendran and Grand Naine. In Chengalikodan, up to 10th subculture passage no polymorphic bands were observed. In cultivars like Poovan and Njalipoovan which exhibited low multiplication rate, no polymorphic bands were observed in regenerants up to S11 stage. For highly multiplying cultivars like Attunendran, Nedunendran and Grand Naine subculturing for multiplication up to 8th subculture stage is recommended. In Chengalikodan, subculturing for multiplication can be advanced up to 9th subculture passage and in Poovan and Njalipoovan multiplication can be advanced up to 10th subculture passage in the protocol standardized at CPBMB. However, the commercial feasibility of the findings and working out the economics of production is possible only by large scale adoption of media components and subculture pattern in commercial micropropagation protocol.